Pengaruh Inovasi Menu terhadap Kepuasan Tamu di Pandan View Mandeh Resort and Resto - Nur Anisa; Hendri Azwar (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by the problem of the influence of menu innovation on guest satisfaction at Pandan View resort and restaurant. This type of research is quantitative with a causal associative form. This research was conducted at Pandan View Mandeh resort and restaurant. The aim of this research is to evaluate the influence of menu innovation at Pandan View Mandeh resort and restaurant. The population in this study was 29,100 people, with a sample of 98 respondents. Data collection used a questionnaire with a Likert scale. Using descriptive analysis and classification of interval class scores using the SPSS version 26 program. Based on the research results, it is known that the overall indicator data with a result of 123.90 is categorized as very good. The size indicator of 12.16 is categorized as good, the price indicator of 15.92 is categorized as good, the appearance indicator of 15.43 is categorized as sufficient, the product availability indicator of 11.69 is categorized as sufficient, the guest satisfaction indicator of 34.35 is categorized as sufficient, the suitability of expectations indicator of 11.65 is categorized as sufficient, the indicator of interest in returning to visit is categorized as sufficient, the availability indicator is recommended 11.16 is categorized as sufficient. The results of this research also show that there is a significant influence of menu innovation (X) on guest satisfaction (Y). The Adjusted R square value of 0.406 indicates that these variables explain 40.6% of guest satisfaction, while the remaining 59.4% is influenced by other factors not examined in this research. Furthermore, F is 67.178 with a significance level of 0.000 <0.05 indicating a strong relationship between variables.